Outcome of Fixed Dose Radioiodine Therapy in Hyperthyroid Patients –Three Years Follow up Study at INMAS Mitford - Sharmin, Samira; Rahman, Manbub ur; Haque, Jesmine Ara; Billah, Syed Muhammad Baquki; Rahman, Hosne Ara; Hossian, Jamiul; Ferdous, Jasmine; Uddin, Monir; Yasmine, Farida (Bangladesh Journal of Nuclear Medicine, 2019)
Background: Hyperthyroidism is a morbid condition. Radioiodine therapy is very safe, popular and effective treatment of hyperthyroidism. This study was design to determine the outcome of fixed dose radioiodine (RAI) therapy in hyperthyroid patients in a single institute. Patients and Methods: This was a retrospective study conducted from January 2014 to December 2016 at 1Institute of Nuclear Medicine and Allied Sciences, Sir Salimullah Medical College Campus, Mitford, Dhaka. A total 71 patients were enrolled for this study. All the patients were pretreated with antithyroid drugs than underwent fixed dose of RAI therapy. They were followed up at regular interval. Chi-square and paired t test was done to see the level of significance. Results: Mean age of the patients were 41.61 years (range 19-60 years). Male were 29 (40.8%) and female were 42 (59.2%). Mean months of pretreated with antithyroid drugs were 30.59 ± 23.68 months, range (2-96 months). Before RAI therapy mean TSH was 0.12 ± 0.14 μ IU/ml range (0.0001-0.54 μIU/ml) and after RAI therapy mean TSH was 1.6 ±1.5μ IU/ml range (0.002-5.00 μIU/ml). Before RAI therapy mean FT4 was 26.26 ±10.25 fmol/ml, range (7.86-47.78 fmol/ml ) and after RAI therapy mean FT4 was 23.45±8.22 fmol/ml, range (8.78-40.45 fmol/ml). All patients diveided into three groups: Graves’ disease (29), toxic multinodular goiter ( 28) and toxic autonomous nodule (14). After three years of follow up 27 (38%) patients were euthyroid, 2 (2.8%) remain hyperthyroid, 3(4.2%) were relapse cases and 39 (54.9%) were hypothyroid. Conclusion: This follow up study showed that patients treated with RAI therapy became hypothyroid in the long run. Relapse and persistent hyperthyroid state were very common phenomenon after RAI therapy. Bangladesh J. Nuclear Med. 21(1): 8-11, January 2018